Prospective Modelling of Oil Supply in Tunisia - Necibi, Thameur (International Journal of Energy Economics and Policy, 2014)
The theoretical framework which we are developing refers essentially to Hubbert model in order to determine the peak oil in Tunisia and the exploitation speed of the remaining resources, while referring to the data supplied by the Directorate General for Energy. The study focuses on the comparison between the results of the several econometric adjustment techniques (linear, non-linear techniques, linear techniques with structural change and the non-parametric methods) applied to the Tunisian oil production during the period going from 1966 to 2011. The prospective study through the econometric models has allowed us to determine the two dates scaring all energy executives, namely the peak which took place in the middle of the eighties and the finiteness of resources planned in 2028. The obtained results have shown that it remains 495 million barrels to be produced in Tunisia, bearing in mind that the data supplied by the authorities announces the figure of 420 million barrels of the remaining proved reserve in the Tunisian underground. Thereby, we have noticed a strong link between the physical models for reservoir flows and the empirical specifications based on the decline curves. Keywords: Oil production; non-linear techniques; non-parametric methods; peak oil. JEL Classifications: C51; Q41; Q47